A two layer soil moisture model for estimating crop evapotranspiration and runoff - DAS, H. P.; CHOWDHURY , A.; BHAGWAT, R. S. (MAUSAM, 1999)
In the present study, a two layer model has been proposed to estimate evapotranspiration, soil moisture storage and runoff. For this purpose soil profile has been assumed to be composed of two layers : the top layer having a fixed field capacity of 100 mm and the underlying layer having field capacity depending on the soil texture. Normal values of rainfall and potential evapotranspiration have been used in the study. The model, applied to kharif and rabi seasons furnishes crop evapotranspiration period when soil in two layers reach wilting point and surface runoff and its duration. The model developed has been applied to 411ocations representing most of the soil types found in India. The analysis revealed that lowest ET is seen over Himalayan foothills and northeast India in kharif and rabi seasons. Enough residual soil moisture is available to the crops at the end of kharif season over NE India; most of it being in the top layer. Eastern India record largest runoff of 800-1000 mm. Arid to semi-arid region in NW India does not seem to experience much runoff.